Engagement and Affective Communication During Pediatric Nephrology Clinic Visits: Associations with Medication Adherence - Glenn, Trevor W. (Patient Educ Couns, 2020)
OBJECTIVE: To evaluate whether engagement and affective communication among adolescents and young adults (AYAs) with chronic kidney disease (CKD), caregivers, and pediatric nephrology providers during outpatient clinic visits predicts antihypertensive medication adherence. METHODS: AYAs (n=60, M age=15.4 years, SD=2.7, 40% female, 43% African American/Black) and caregivers (n=60, 73% female) attended audio-recorded clinic visits with pediatric nephrologists (n=12, 75% female). Recordings were analyzed using global affect ratings of the Roter Interactional Analysis System. Antihypertensive medication adherence was monitored electronically before and after clinic visits. A linear regression model evaluated associations between affect ratings and post-visit adherence. RESULTS: AYAs took 84% of doses (SD=20%) pre-visit and 82% of doses (SD=24%) post-visit. Higher AYA engagement (β=0.03, p=.01) and the absence of provider negative affect (β=−0.15, p=.04) were associated with higher post-visit adherence, controlling for pre-visit adherence, AYA sex, age, and race, and clustered by provider. CONCLUSIONS: Post-visit adherence was higher when AYAs were rated as more engaged and providers as less negative. PRACTICE IMPLICATIONS: AYAs with lower engagement may benefit from further adherence assessment. Communication strategies designed to more actively engage AYAs in their care and diminish provider conveyance of negative affect during clinic visits may positively influence adherence among AYAs with CKD.